(untitled) (Journal of Agriculture and Environment, 2022)
Sclerotium rolfsii Sacc. is prevalent in leguminous and solanaceous crops but over the last five years, its severity has increased in several crops such as rice, onion and chilli in Nepal. A study on cross infectivity of S. rolfsii was carried out in March, 2019 at Agriculture and Forestry University, Chitwan. S. rolfsii were isolated from eight crop species viz. rice, lentil, rajma, onion, chickpea, rapeseed, soybean, and chilli. Cross infectivity of the eight isolates was done on the seven crop species in artificially inoculated soils in a screen house. Morphological characters such as mycelial growth rate, number of sclerotia formed, and size of sclerotia were studied. Morphological characters of the S. rolfsii varied among the isolates. All crop species tested were found to be susceptible to all isolates except onion isolate. Germination percentage was greatly reduced (80%) in rajma. Post emergence seedling mortality ranged between 10% in rice and chilli and 100% in chickpea, mustard lentil and rajma. The results of the present study indicate that management strategies of this pathogen should incorporate selection of non-host crops such as maize for crop rotation which helps to prevent build-up of inoculum.